On the edge of glory (…or catastrophe): regulation, transparency and party democracy in data-driven campaigning in Québec - Eric Montigny; Philippe Dubois; Thierry Giasson (Internet Policy Review)
The 2018 election marked an organisational change for major political parties in Québec. They have all massively integrated data-driven campaigning practices. This article identifies factors that could explain the increasing pressure to regulate Québec’s political parties’ uses of large sets of digital voter information. Québec presents an interesting case to study the effects of data-driven campaigning of parties operating in a parliamentary system where privacy protection rules are limited. Based on semi-directed interviews conducted with strategists from the major parties, it also stresses important intra-party changes and challenges for party democracy.